2005
DOI: 10.2135/cropsci2004.0170
|View full text |Cite
|
Sign up to set email alerts
|

Root Segregation of C3 and C4 Species Using Carbon Isotope Composition

Abstract: Partitioning roots for studying cropping systems containing more than one species is important since root growth interaction could influence system performance. The study objective was to test a method for segregating plant species roots from soil samples taken in a mixed stand of corn (Zea mays L.), a C4, and kura clover (Trifolium ambiguum M. Bieb.), a C3 plant. Soil cores containing both corn and kura clover roots were obtained at three distances from the corn row and at two depths in a Rozetta silt loam so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Other 13 C discrimination studies have also shown differential distribution of C 4 and C 3 plant roots with depth or location in field plots (Derner et al 2003;Eleki et al 2005;Polley et al 1992). However, in these studies, the proportion of roots near the soil surface generally was much greater for C 4 plants than for C 3 plants.…”
Section: Ricementioning
confidence: 82%
See 1 more Smart Citation
“…Other 13 C discrimination studies have also shown differential distribution of C 4 and C 3 plant roots with depth or location in field plots (Derner et al 2003;Eleki et al 2005;Polley et al 1992). However, in these studies, the proportion of roots near the soil surface generally was much greater for C 4 plants than for C 3 plants.…”
Section: Ricementioning
confidence: 82%
“…Rice mapping populations studies on d 13 C levels (an expression of 13 C: 12 C isotope ratios) and associated crop productivity traits have indicated quantitative trait loci for d 13 C on five (Xu et al 2009) or on six (Laza et al 2006) of the 12 rice chromosomes. d 13 C analysis has also been used to determine the proportions of C 3 and C 4 plant roots in a number of systems (Derner et al 2003;Eleki et al 2005;Polley et al 1992;Svejcar and Boutton 1985;Svejcar et al 1988), and has been used in programs to improve water use efficiency in rice (Dingkuhn et al 1991;Impa et al 2005;Kondo et al 2004;Scartazza et al 1998).…”
mentioning
confidence: 99%
“…where d 13 C sample is the isotope ratio (in parts per thousand; %) relative to the PDB standard. R sample and R standard are the 13 C/ 12 C molar abundance ratios of the plant sample and the PDB standard (R pd ; 0.0112372), respectively (Eleki et al 2005). Average d 13 C values for C 3 and C 4 plants were reported to be approximately 227% and 213%, respectively (Boutton 1996).…”
Section: Methodsmentioning
confidence: 99%
“…Equations 10-25 were derived with R pd and other R values expressed on both a molar abundance ratio basis and a mass fraction basis. R pd molar abundance ratio 5 13 C/ 12 C 5 0.0112372 (Eleki et al 2005), and R pd mass fraction ratio 5 (R pd molar abundance ratio)(13/12). Because calculated results were , identical to four decimal places, both models were considered equally acceptable.…”
Section: R~cmentioning
confidence: 99%
See 1 more Smart Citation